PENGARUH TERAPI SCALING TERHADAP KONDISI MIKROBIOTA RONGGA MULUT ANAK STUNTING - Octaricha, Tasha (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Stunting is characterized by a child's height being shorter than peers of the same age, leading to saliva gland dysfunction and periodontal disease. Scaling and root planing (SRP) is the gold standard therapy for periodontal disease, effectively reducing pathogenic bacterial populations. Aim: This study aimed to evaluate the effect of scaling and root planing therapy on the oral microbiota profile in the saliva of stunted children. Methods: This study was conducted on elementary school children with stunting who underwent SRP. The oral microbiota profile of saliva was analyzed using next-generation sequencing. Data were statistically analyzed using a paired t-test. Result: The study did not demonstrate statistically significant changes in clinical parameters or oral microbiota profiles after SRP. However, there was a trend of reduction in mean Gingival Index (GI) and Oral Hygiene Index Simplified (OHIS) scores, indicating improvements in clinical conditions. Sequencing results revealed three predominant genera in the saliva of stunted children: Prevotella, Veillonella, and Streptococcus. Conclusion: Scaling and root planing therapy did not significantly affect the oral microbiota profile in the saliva of stunted children